Pembelajaran IPA SMP Berbasis Kearifan Lokal Ternate: Sebuah Gagasan Penyusunan Desain Pembelajaran Berbasis Kearifan Lokal - Jailan Sahil; Dharmawaty M. Taher; Ilham Majid; Said Hasan (Peneliti.net, 2022)
Lack of knowledge about local wisdom and national identity is one of the causes of the emergence of problems of moral and character decline experienced by most of the young generation today. One of the ways that teachers do in instilling student character is by applying local wisdom-based learning. The obstacle that is often experienced by junior high school science teachers in Ternate City in learning is the difficulty of integrating local wisdom into the material to be taught to students, as a solution to raise the local potential of an area, teachers are required to always innovate to be able to design learning based on local wisdom. Ternate has a variety of local wisdom potentials that can be used as learning resources by designing learning scenarios based on Ternate local wisdom, one of which is by mapping basic competencies to ensure the suitability of subject matter to be integrated with local wisdom objects. The integration of local wisdom in learning is done by making local wisdom a context for discovering scientific concepts. The stages in designing learning are identifying the potential of local wisdom, analyzing scientific concepts contained in local wisdom objects, mapping Basic Competencies and local wisdom, designing learning scenarios and designing teaching materials in the context of local wisdom